The Relationship between Energy Consumption Status and Nutritional Status of 6--18 Years Age Orphanage Children in Jakarta 1999 - Mochamad Rachmat; Ratna Djuwita (Media Gizi dan Keluarga, 2000)
This study was conducted to investigate the nutritional status and food consumption of children in the Jakarta orphanages.The aim of the study is to examined the relationship between energy consumption and nutritional status included its related factors of orphanage children 6 to 18 years of ages in Jakarta in 1999.The design of this study was cross sectional, 308 respondents were involved from 48 PSAA. Nutritional status as the dependent variable determined by height for age and weight for age using z-score. The independent variables which related to nutritional status were: energy consumption status, protein consumption status, length of stay in the orphanage, age, and gender.The result of this study shows that the prevalence of protein energy malnutrition (PEM) is 49.7% (height for age) and 32.8% ( weight for age ). Energy consumption, protein consumption, and iron consumption were 54.5%, 62.0%, and 68.2% resvectively. Significance relationship was found between energy consumption status and nutritional status (OR= 1.7; at p-value=0.0001; 95%CI: 1.3-2.2) using height for age indices and OR = 2.2 (p=0.0067; 95%CI: 1.2-3.8) using weight for age indices. Based on weight for age, the risks of respondent who stayed at orphanage for 36 months or more to become PEM was 0.59 times (p=0.0325; 95%CI: 0.36-0.95) compared to them whose stayed less then 36 months in the orphanage.The risks of female respondents to become PEM was 0.59 times (p=0.0230; 95%CI:0.38-0.93) using height for age and 0.42 times (p=0.0005; 95%CI: 0.25-0.68) using weight for age compared to male respondents.The result of logistic multiple regression analysis to nutritional status as a dependent variable using height for age as follows: ln p/1-p = -0.4482 + 0.9090 (energy consumption status) + 0.3129 (protein consumption status) - 0.7004 (age) - 0.4208 (gender). While based on weight for age, the regression equation was: ln p/1-p = -0.9249 + 0.9116 (energy consumption status) + 0.5611 (protein consumption status) - 0.6561 (length of stayed in orphanage) - 0.8256 (gender) - 0.3110 (age). Refers to the result of this study, we recommend to every institution or non goverment organization (NGO) which relate to orphanage could give their participation, funding and guidance in order to increase the quantity and quality of food consumed by the orphanage child. This study recommend a further study in order to know the real condition of this problem especially in others independent variables.Keywords: consumption, nutritional status, children